Urbane Reality: Social Footprints of Teenagers and the Search for Solutions to Deviant Behavior at VHS 5 Padang - Lenggogeni, Putri; Mudjiran, Mudjiran (Postgraduate School, Universitas Negeri Padang, 2024)
This study aims to explore the factors that cause adolescent deviant behavior, forms of deviation that may occur, and efforts that can be made to overcome these problems. The title tries to present an interesting nuance by using words such as